SCREENING OF EXTRACELLULAR HYDROLYTIC ENZYMES FROM MARINOBACTER HYDROCARBONOCLASTICUS MARINOBACTER HYDROCARBONOCLASTICUS STRAIN AK5 - S. ANIL KUMAR; R. ARUNASRI; Y. JAYACHANDRA; M. B. SULOCHANA (The Bioscan, 2010)
The aim of this study was to screen the extracellular hydrolytic enzymes from extreme halotolerant Marinobacter hydrocarbonoclasticus strain AK5, isolated from Arabian Sea Mumbai, Maharashtra, India. Identification of the bacterium was done based upon biochemical tests and 16S rRNA sequence. It is a gram-negative, aerobic, non-spore forming, motile, rod-shaped bacterium. The strain AK5 grows at optimum temperature 35°C and pH 8.5. It grows at NaCl concentrations of 0.08 to 4.1 M. The novel extremozymes such as proteases, amylases, xylanases, lipases, esterases, glutaminases asparaginases and inulinases were screened. The strain AK5 able produce three hydrolytic enzymes such as esterase, asparaginase and glutaminase which have potential applications in various biotechnological processes.